Biodiversity, international tourism and development - Andreas Freytag; Christoph Vietze (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
We analyze whether biodiversity is increasing the receipts of tourism and beneficial for Least Developed Countries (LDCs). The underlying assumption is that a rich biodiversity provides a comparative advantage for most LDCs. We use a simple trade theory framework. The model is supported by an empirical analysis. The main findings are that first LDCs seem to have a comparative advantage in (sustainable) tourism, that second incidence of birds as the probably best explored taxonomic group has a positive impact on inbound tourism receipts per capita, and that third the rate of endangered to total birds is negatively influencing tourism receipts.
Keywords: F18; Q26; 330; tourism; economic growth; biodiversity conservation; Biodiversität; Öko-Tourismus; Komparativer Kostenvorteil; Tourismuswirtschaft; Entwicklungsländer